Program Blended Parenting PAUD Istiqomah Sambas Purbalingga - Siti Khasiroh; Novan Ardy Wiyani (UIN Sultan Maulana Hasanudin Banten, 2023)
Alignment of education and care between Early Childhood Education institutions and families is an important factor in a child's success. Parenting activities are one of the programs run by early childhood education institutions as an effort to harmonize education and care between parents and educators. The implementation of parenting programs needs to be innovated to provide awareness and knowledge about appropriate stimulation for child development, so that there is continuity of education and care at home and in early childhood education institutions. This research examines the blended parenting program as an innovative parenting program implemented by the Istiqomah at Sambas Purbalingga. This qualitative research was conducted by interviews, observations and document searches to collect data. The proscess of data analysis is done through reduction, analysis and classification. The purpose of this research is to explore and describe the implementation of the blended parenting program conducted by the Istiqomah Sambas Purbalingga Early Childhood Education institution. The results of the research show that the blended parenting program is carried out through the stages of planning, organizing, implementing and evaluating the program. The blended parenting program provides knowledge to parents about stimulating education and proper parenting, strengthens cooperation between parents and institutions, aligns education and care at home and at institutions and realizes children's learning readiness towards basic education.